Ермак: исторический роман / Евгений Федоров - Федоров Евгений Александрович (ЭКСМО - Пресс, 1998)
Экземпляры: филиал №4 (20140305) / Инвентарный номер: 37111 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: Ф 33 / ГРНТИ: 17 / ББК: 84(2Рос)